2009
DOI: 10.1007/s00595-008-3860-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent results of therapy for scirrhous gastric cancer

Abstract: The prognosis of patients with scirrhous gastric cancer (SGC) is extremely poor. However, recent advances in therapeutic strategies against SGC, using effective anticancer drugs, have prolonged the survival of patients with SGC. This paper reviews the recent therapeutic outcomes of this type of gastric cancer and introduces a new treatment protocol for SGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…LSGC, localized type IV scirrhous gastric cancer; LP, linitis plastica; OGC, other types of advanced gastric cancer. and strong chemotherapy, including S-1, may be a more favorable option than aggressive surgery or palliative gastrectomy (2,3,13,16). In the present study, peritoneal cytology was an independent prognostic factor in SGC.…”
Section: A B C Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…LSGC, localized type IV scirrhous gastric cancer; LP, linitis plastica; OGC, other types of advanced gastric cancer. and strong chemotherapy, including S-1, may be a more favorable option than aggressive surgery or palliative gastrectomy (2,3,13,16). In the present study, peritoneal cytology was an independent prognostic factor in SGC.…”
Section: A B C Discussionsupporting
confidence: 47%
“…Despite recent advances in the diagnosis and treatment of gastric cancer, the majority of cases of SGC are not detected at an early stage since tumor cells migrate throughout the submucosa without severely affecting the mucosal lining of the stomach. This causes difficulty in detecting cancer cells by gastrointestinal series or endoscopy (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…1b). Scirrhous carcinomas account for about 10% of all gastric carcinomas, and carry a worse prognosis than other types of gastric carcinoma, reflecting their rapid proliferation of cancer cells [3][4][5]. The common features of scirrhous gastric cancer include rapidly progressive invasion, and a high frequency of metastasis to the peritoneum [6].…”
Section: Introductionmentioning
confidence: 99%
“…New anti-cancer drugs are being used for advanced and recurrent gastric cancer in many institutions [1]. A recent paper has suggested that neoadjuvant chemotherapy, such as preoperative intraperitoneal chemotherapy (IPC) combined with systemic chemotherapy using S-1 and docetaxel may have a strong survival benefit for patients with scirrhous gastric cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, many questions remain unanswered, such as whether neoadjuvant chemotherapy is better than adjuvant chemotherapy, and whether IPC is better than systemic chemotherapy [2]. Moreover, there is as yet no effective treatment against peritoneal dissemination.…”
Section: Introductionmentioning
confidence: 99%